Strategi Manajemen Waktu bagi Mahasiswa yang Bekerja Paruh Waktu (Studi Kualitatif) - Irvan Firdaus; Jimmy Alfaruqi Ramadan; Lastri Sulastri; Rizky Ramdani Miftahul Fadilah; Yudi Prastyo (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This study aims to determine the time management strategies used by students who work part-time in balancing college and work. with the formulation of the problem “challenges to manage time between work and study”. This study used a qualitative approach involving 70 respondents. The results showed that 60% of respondents were in semester 3-4 and 80% worked in private companies. A total of 64.3% felt able to manage their time well, although 50% often felt overwhelmed. Commonly used strategies include schedule planning (58.5%), prioritizing (51.4%), and using tools such as calendars or apps (41.4%). In addition, 67.1% claimed to have improved their time management skills. This study concludes that working part-time not only provides economic benefits, but also strengthens students' time management skills.